Operational and economic evaluation of ammonia bunkering – bunkering supply chain perspective - Yang, Mengyao (2023)
Using ammonia as an alternative marine fuel has been gaining interest in reducing greenhouse gas emissions in the maritime sector. This paper describes the development of a discrete event simulation model for bunker supply chain, emphasising how ammonia bunkering affects the operational and economic performance of the system. The results show that the model is a useful tool for ammonia bunker supply chain management, including the selection of the number and capacity of ammonia bunker supply vessels, bunkering flow rate and ammonia demand. Flow rate has a significant impact on bunkering service time, with an effect of up to 51.3% when it is changed by ±50%. The greater the demand for ammonia, the more significant the impact of ammonia bunkering flow rate on bunkering service time. Moreover, the number of ammonia bunker supply vessels is the most sensitive parameter for annual operational cost, with an effect of up to 15.2%.